Influencing Factors of Sexual Intimacy and Satisfaction among Women within 1 Year after Mastectomy - Sunyoung Kim; Sukhee Ahn (Korean Society of Women Health Nursing, 2019)
PURPOSE: The purpose of this study was to identify the levels of body image, sexual intimacy, and sexual satisfaction, and to explore factors affecting sexual intimacy and satisfaction among women within one year of mastectomy. METHODS: The present study was a cross-sectional survey and involved 101 women who had undergone mastectomy at a University hospital of D city, Korea. Measurement included the scales of body image, sexual intimacy, and sexual satisfaction. RESULTS: Mean age of the subjects was 51 years. Scores of the body image, sexual intimacy, and sexual satisfaction were 59.62, 90.69, and 69.04, respectively. Body image, sexual intimacy, and sexual satisfaction were significantly related to each other. Sexual intimacy was higher when women were of young age (β=−.32), had a shorter period since surgery (β=−.24), and with higher levels of body image (β=.37). Sexual satisfaction was higher when women had higher levels of body image (β=.19) and greater levels of sexual intimacy (β=.74). CONCLUSION: Higher levels of body image and greater levels of sexual intimacy were identified as the significant factors influencing sexual satisfaction among these women. Future research with a mixed-method research is needed to gain a deep understanding of the sexuality between women and their husbands.